2020
DOI: 10.3390/ijms21062068
|View full text |Cite
|
Sign up to set email alerts
|

Pic-Producing Escherichia coli Induces High Production of Proinflammatory Mediators by the Host Leading to Death by Sepsis

Abstract: Escherichia coli is an important pathogen responsible for a variety of diseases. We have recently shown that Pic, a serine protease secreted by E. coli, mediates immune evasion by the direct cleavage of complement molecules. The aim of this study was to investigate the action of a Pic-producing bacteria in a murine model of sepsis. Mice were infected with Pic-producing E. coli (F5) or F5∆pic mutant. Animal survival was monitored for five days, and a subset of mice was euthanized after 12 h for sample acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…A similar result was observed by Dutra et al. ( 82 ) when the ExPEC strain F5, a Pic-producing ExPEC, and its respective pic mutant were tested in a murine sepsis model. While all animals infected with the wild type strain died, all animals infected with the mutant strain survived, suggesting that Pic is also involved in the pathogenesis of sepsis.…”
Section: Discussionsupporting
confidence: 85%
“…A similar result was observed by Dutra et al. ( 82 ) when the ExPEC strain F5, a Pic-producing ExPEC, and its respective pic mutant were tested in a murine sepsis model. While all animals infected with the wild type strain died, all animals infected with the mutant strain survived, suggesting that Pic is also involved in the pathogenesis of sepsis.…”
Section: Discussionsupporting
confidence: 85%
“…Another study from Universidade Ceuma in Brazil showed decreased survival rate of infected mice up to 34% during 12 hours period after intraperitoneal injection of E. coli and 100% mortality after 24 hours [27]. In this study, the survival rate of mice in positive control group decreased into 55.6% 12 hours after bacteria injection and after 18 hours post injection, the survival rate was 11.1%.…”
Section: Figuresupporting
confidence: 51%
“…In addition, ExPEC VFs, which were involved in human ExPEC infections, such as urinary tract infections, sepsis, and meningitis, were also highly identified in ESBL/AmpC-EC than in the non-ESBL/ AmpC-EC (p < 0.05). Especially, the prevalence of the three VFs, namely papC, pic, and ompT, which were reported to show a positive association with the high mortality in human ExPEC infection (Kudinha et al, 2013;Krawczyk et al, 2015;Dutra et al, 2020), was significantly higher in the ESBL/ AmpC-EC isolates (p < 0.05). Furthermore, the OR of biofilm formation was 3.8-fold greater (95% CI: 1.42-10.30, p < 0.05) in the ESBL/AmpC-EC isolates than in the non-ESBL/ AmpC-EC isolates.…”
Section: Discussionmentioning
confidence: 94%